Functions, Meanings, and Preservation of Oral Literature in the Galeng Tahun (10 Suro) Tradition of Dukuh Beber, Indonesia - Yoga Pranoto, Bambang; Maharani Umaya, Nazla; Andrian, Setia Naka (Lembaga Teewan Journal Solutions, 2026)
Oral literature constitutes an important component of Indonesia's intangible cultural heritage, preserving collective memory, cultural identity, and local wisdom across generations. One of the oral traditions that continues to be practiced is the Galeng Tahun (10 Suro) tradition in Dukuh Beber, Central Java. This study aimed to analyze the functions, meanings, and preservation strategies of oral literature embedded in this tradition. A qualitative ethnographic approach was employed to explore the cultural practices and community perspectives surrounding the ritual. Data were collected through participant observation, in-depth interviews with traditional leaders, religious figures, community elders, and local residents, as well as documentation of ritual activities and oral narratives. The data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, while source and technique triangulation were applied to ensure trustworthiness. The findings reveal that oral literature in the Galeng Tahun tradition embodies multidimensional meanings, encompassing religious devotion, gratitude, moral education, social cohesion, and cultural identity. Its functions extend beyond ritual communication to include the transmission of ethical values, the strengthening of communal solidarity, and the preservation of collective memory. Preservation efforts are sustained through intergenerational transmission, active community participation, educational initiatives, and digital documentation. The study proposes a community-based collaborative preservation model, integrating families, traditional leaders, educational institutions, local government, and younger generations to ensure the sustainability of oral literature amid contemporary social and cultural changes.